Características de carcaça de cordeiros Santa Inês alimentados com diferentes níveis de energia metabolizável - Oliveira, Elaine Cristina Santiago (2013)
The study was conducted to assess the impact of diets with varying metabolizable energy levels on the quantitative and qualitative carcass characteristics of Santa Inês lambs. Thirty-five animals with an average age of approximately 60 days were used, with an initial weight of 14.77 +1.26 kg, castrated, and slaughtered when the average of one treatment reached 28kg bodyweight. The animals were divided into five experimental treatments with different levels of MS (1.13, 1.40, 1.73, 2.22, and 2.60), in a randomized block design. The Tifton 85 hay was used as roughage. Variables such as empty body weight (EBW), hot and cold carcass weight (HCW and CCW), hot carcass yield (HCY), carcass cooling loss (CCL), and biological yield (RB) were obtained to assess the quantitative carcass traits as well as the commercial cuts and non-carcass component yields. The technique of ultrasound was used for the assessment of housing in vivo by measuring the ribeye area (REA), subcutaneous backfat thickness (SBT), and the longissimus dorsi depth (LDD) of Santa Inês sheep. The ultrasound equipment used was an ALOKA brand SSD 500 model, featuring an acoustic probe of 12 cm and a frequency of 3.5 MHz for in vivo measurements of these parameters. All calculations of error, Pearson correlation, and regression analyses were performed using SAS Software. There was a linear increasing effect (P <0.05) of ME levels on empty body weight, carcass weight, hot and cold yields, carcass cooling loss, and biological yield. Rising levels of EM promoted significant differences in retail cuts' weight, and a linear increasing effect on flank yields. Variables, including gastrointestinal tract contents, omasum, rumen, reticulum, expressed in kg and %, as well as abomasum and intestine relative weights, and the absolute weight of the small intestine, showed a significant effect (P < 0.05) with a linear increase in diets containing different levels of ME. There was an adverse linear effect (P < 0.05) of NDF levels on the weights of the heart, TELT (trachea, esophagus, lungs, and tongue), liver, kidney, and spleen, expressed in kilograms. The decomposition error was used to determine the accuracy of ultrasound measurements. Among REAU (ultrasonographic measurement) and REAC (measured on the carcass), it was observed that ultrasound measurements overestimated the measurements in relation to the housing. For SBT, ultrasonographic measurements (SBTU) were underestimated about the housing (SBTC). The values obtained by measurements on the carcass for depth measurements and the length of the longissimus dorsi (LDD and LDL) were higher than those obtained by ultrasound. Linear effects on measurements obtained in vivo and post-slaughter relative to the level of metabolizable energy of diets to which the animals were subjected. There was a high correlation between REAU and REAC measurements (r = 0.95), and between SBTU and SBTC, the correlation was average (r = 0.56). Between the measures of the depth of the longissimus dorsi (PDL) using carcass evaluation methods (ultrasonography and post-slaughter), a correlation of r = 0.79 was observed. It is concluded that the increase in energy levels influences carcass traits in the diets of Santa Inês sheep confined, and ultrasonography is an effective tool that can be used to predict muscle, time to slaughter, and breeding herd.